2014
DOI: 10.1021/ol5014312
|View full text |Cite
|
Sign up to set email alerts
|

Rh(III)-Catalyzed Selective Coupling of N-Methoxy-1H-indole-1-carboxamides and Aryl Boronic Acids

Abstract: A Rh(III)-catalyzed selective coupling of N-methoxy-1H-indole-1-carboxamide and aryl boronic acids is reported. The coupling is mild and efficient toward diverse product formation, with selective C-C and C-C/C-N bond formation. Kinetic isotope effects studies were conducted to reveal a mechanism of C-H activation and electrophilic addition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(47 citation statements)
references
References 68 publications
2
42
0
3
Order By: Relevance
“…Thea rylation of indole at the C2position with arylboronic acid was accomplished, aided by an N-methoxy amide as adirecting group. [225] Asummary of the reactions is presented in Table 1.…”
Section: Indole and Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thea rylation of indole at the C2position with arylboronic acid was accomplished, aided by an N-methoxy amide as adirecting group. [225] Asummary of the reactions is presented in Table 1.…”
Section: Indole and Its Derivativesmentioning
confidence: 99%
“…However,the majority of studies related to the C7-functionalization of indole have involved converting the indole 193 into the indoline derivative 199.I nt his case,t he reduction of indole was initially performed followed by selective C À Hf unctionalization and then oxidation to provide the target functionalized indole derivative (Scheme 61). [216] (alkenylation) 2013, Li and Wang [217] (alkenylation) 2012, Li [218] (acylation) 2013, Zhou and Li [219] (alkylation) 2012, Zhou and Li [220] (amination) 2014, Xu [221] (cyanation) 2015, Sharma and Vander Eycken [222] (carboxamidation) 2016, Wang and Wang [223] (alkylation) 2016, Li [224] (alkyne insertion) 2014, Cui [225] (arylation) Scheme 60. Rh III -catalyzed C7-alkenylation of indole derivatives with olefins.…”
Section: Indole and Its Derivativesmentioning
confidence: 99%
“…In 2014, our group reported that N-methoxy indole-Ncarboxamides 81 and aryl boronic acids 82 could selectively transform to different products via slightly changing reaction conditions (Scheme 21). [30] By using 2 mol % [Cp*RhCl 2 ] 2 as catalyst, 4 equivalents of Cu(OAc) 2 as oxidant and MeOH as solvent, the 2-aryl indole derivatives 83 formed via CÀ H activation at 60°C in good yields. Replacing Cu(OAc) 2 by 4 equivalents of Ag 2 O could promote a CÀ H activation/ [4 + 2] cyclization to deliver indole derived heterocycles 84 smoothly.…”
Section: Reaction Of Indole-n-carboxamides With Other Compoundsmentioning
confidence: 99%
“…By switching the external oxidant, they were able to obtain either 2-arylated product or subsequently cyclized product (Scheme 48). [63] …”
Section: Rhodium Catalysismentioning
confidence: 99%